2018
DOI: 10.1051/0004-6361/201833795
|View full text |Cite
|
Sign up to set email alerts
|

Measuring precise radial velocities on individual spectral lines

Abstract: Context. Stellar activity is the main limitation to the detection of an Earth-twin using the radial-velocity (RV) technique. Despite many efforts in trying to mitigate the effect of stellar activity using empirical and statistical techniques, it seems that we are facing an obstacle that will be extremely difficult to overcome using current techniques. Aims. In this paper, we investigate a novel approach to derive precise RVs considering the wealth of information present in high-resolution spectra. Methods. Thi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
182
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(183 citation statements)
references
References 58 publications
1
182
0
Order By: Relevance
“…Additional results in the literature have shown that other processes besides RV conv may indeed play a dominant role near the solar minimum. For example, recent techniques demonstrate the ability to remove most power at the rotation period, but leave 1 m s −1 RV variability in corrected timeseries: Dumusque (2018) and Cretingier et al (2019, in revision) identify spectral lines insensitive to the suppression of convective blueshift; by computing RVs using these specially-selected line lists, the authors are able to reduce the RV RMS by a factor of 2.2, down to 0.9 m s −1 . Independently, Milbourne et al (2019) use solar images from HMI/SDO to reproduce the activity-driven RVs.…”
Section: Discussionmentioning
confidence: 99%
“…Additional results in the literature have shown that other processes besides RV conv may indeed play a dominant role near the solar minimum. For example, recent techniques demonstrate the ability to remove most power at the rotation period, but leave 1 m s −1 RV variability in corrected timeseries: Dumusque (2018) and Cretingier et al (2019, in revision) identify spectral lines insensitive to the suppression of convective blueshift; by computing RVs using these specially-selected line lists, the authors are able to reduce the RV RMS by a factor of 2.2, down to 0.9 m s −1 . Independently, Milbourne et al (2019) use solar images from HMI/SDO to reproduce the activity-driven RVs.…”
Section: Discussionmentioning
confidence: 99%
“…Eventually, we have selected a total of ∼ 3 000 reliable targets of F, G, K, M and L spectral types, to use for our subsequent NZP analysis. Figure 1 shows a Hertzsprung-Russel (HR) diagram of the HARPS sample stars over-plotted on top of the known stars within 100 pc, retrieved from the Gaia DR2 catalog (Gaia Collaboration et al 2016, 2018. During its operational time, HARPS observed mainly bright nearby main-sequence stars and late-type G and K giant stars.…”
Section: The Harps Data and The Stellar Samplementioning
confidence: 99%
“…In addition to our CCF RV solution, we have developed a new forward-modeling technique by adapting algorithms developed for the iodine RV technique (Marcy & Butler 1992;Butler et al 1996) as well as ideas from the "line-by-line" method developed by Dumusque (2018). Forward-modelling from empirical stellar spectral templates is known to produce velocities with less statistical scatter than the CCF method, and typically measures relative rather than absolute radial velocities (Anglada-Escudé & Butler 2012).…”
Section: Forward Modelingmentioning
confidence: 99%